Open Access in Vocational Education and Training Research - A Research Project at BIBB - Getz, Laura [Verfasser]; Langenkamp, Karin [Verfasser]; Rödel, Bodo [Verfasser]; Taufenbach, Kerstin [Verfasser]; Weiland, Meike [Verfasser] (My University, 2019)
"This short paper elaborates on a research project at the Federal Institute for Vocational Education and Training (BIBB) in Germany, which examines perspectives of researchers on open access (OA) in the field of Vocational Education and Training (VET). The project explores the technical and structural, policy-related and normative, and inherent academic research conditions influencing the acceptance, dissemination, and use of OA in German-speaking countries. VET research comprises of various related academic research areas, rather than one stand-alone discipline. Therefore, results of the project will be transferable to other fields of the social sciences and humanities. The project is rooted in science communication and media theory. A sequential mixed methods design with both qualitative and quantitative strands forms its empirical basis. Accordingly, an online survey aimed at academic researchers from various disciplines in VET research will follow a qualitative exploration via focus groups. The project is running from 2018-2021." (Authors' abstract, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 4 Bezugswissenschaften; Berufsbildungsforschung; Open Access; Veröffentlichung; Wissenschaftliches Arbeiten; Elektronisches Publizieren; Forschungsprojekt